(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2024)
In the digital era, the humanisation of brands emerges as a vital component to establish emotional connections with their audiences. This research is a result of the research project Methodology for measuring positioning through multivariate analysis for the development of brand value: a business approach. It studies and explores various strategies implemented by TES (Tecnológico Universitario Espíritu Santo) to infuse humanity into its brand identity. It demonstrates how the incorporation of elements of social activities and the determined use of social media content has contributed significantly to the positive perception of the TES brand towards students.